1991
DOI: 10.1063/1.105751
|View full text |Cite
|
Sign up to set email alerts
|

Ordering effects on the electrical characteristics of Ga0.5In0.5P grown by metalorganic chemical vapor deposition

Abstract: Articles you may be interested inEffects of ordering on the operation of AlGaInP lasers grown by metalorganic chemical vapor deposition Ordering effect on the performance of Ga0.5In0.5P visible lightemitting diodes grown by metalorganic chemical vapor deposition Selenium and zinc doping in Ga0.5In0.5P and (Al0.5Ga0.5)0.5In0.5P grown by metalorganic chemical vapor deposition J. Appl. Phys. 66, 5285 (1989); 10.1063/1.343718 Disordering of the ordered structure in metalorganic chemical vapor deposition grown Ga0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Consequently, the lattice matched band gap is 1.97 eV which is consistent with little or no ordering. [6][7][8] The 77 K photoluminescence linewidth of 11 meV compares well with metalorganic chemical vapor deposition ͑MOCVD͒ and gas source molecular-beam epitaxy ͑GS-MBE͒ results. 8,9 A weak peak approximately 30 meV below the bandedge is also observed and has been attributed to a donor-acceptor pair transition.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Consequently, the lattice matched band gap is 1.97 eV which is consistent with little or no ordering. [6][7][8] The 77 K photoluminescence linewidth of 11 meV compares well with metalorganic chemical vapor deposition ͑MOCVD͒ and gas source molecular-beam epitaxy ͑GS-MBE͒ results. 8,9 A weak peak approximately 30 meV below the bandedge is also observed and has been attributed to a donor-acceptor pair transition.…”
Section: Resultssupporting
confidence: 69%
“…[6][7][8] The 77 K photoluminescence linewidth of 11 meV compares well with metalorganic chemical vapor deposition ͑MOCVD͒ and gas source molecular-beam epitaxy ͑GS-MBE͒ results. 8,9 A weak peak approximately 30 meV below the bandedge is also observed and has been attributed to a donor-acceptor pair transition. 10 The electrical properties of the GaInP layers were examined by Hall effect and capacitance-voltage (C -V) profiling.…”
Section: Resultssupporting
confidence: 59%
“…The effect has been attributed to diffusion in the bulk. 14,17,18 Recently, Te added during OMVPE growth of GaInP was observed to increase the [ -110] step velocity dramatically, which resulted in the growth of disordered material. [9][10][11] This is one of the few examples of surfactant effects during OMVPE growth.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ordered crystals often showed rather smaller mobilities, compared with the disordered alloys, probably due to an interface scattering. 17,18 The ordered alloys made in this study, on the contrary, exhibit higher electron mobilities than that of the disordered alloys, indicating that the scattering at the interfaces between ZnSe and ZnS layers is negligible. Figure 5 shows the temperature dependence on the Hall mobility for ͑ZnS͒ 3 ͑ZnSe͒ 42 ͑a͒ and ZnS 0.07 Se 0.93 ͑b͒.…”
Section: A Structures and Pl Propertiesmentioning
confidence: 69%